Recovery Of Intra Parenchym Lesion Hemorragic Stroke - Dewi Nur Fiana (Fakultas Kedokteran, 2020)
Recovering from a stroke can be a lengthy process that requires patience, hard work, and commitment. It may take years to recover. Recovery time after a stroke is different for everyone—itcan take weeks, months, or even years. Some people recover fully, but others have long-term orlifelong disabilities. Strokes can cause significant impairment in language, cognition, motor, andsensory skills. This is why it’s considered to be a leading cause of serious long-term disability. Thehemorrhage at the left cortex and subcortex of temporal lobe gives manifestation to contralateralhemiparesis. In acute setting, we should optimize the cerebral blood oxygen perfusion, so thepenumbra area can survive. After surviving the acute stage, we have to assest functional prognosisin activities and optimized it because patient still has the contralateral extremities to help withactivities. Keywords: Functional ability, Hemorrhagic stroke, Rehabilitation,